PENANAMAN NILAI-NILAI KEDISIPLINAN SISWA KELAS V SEKOLAH DASAR NEGERI 2 MUMBUL SARI LOMBOK UTARA - Yuli Parwati, Poppy; Nurhasanah; Sobri, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to empirically examine the Cultivation of Disciplinary Values of Fifth Grade Students of SDN 2 Mumbul Sari North Lombok. The subject of this research is the Cultivation of Disciplinary Values of Class V Students. The type of research used in this study is a qualitative research method with a descriptive approach to explore deeply and thoroughly related to penomena in the field, and the data sources used are primary data and secondary data. The data collection techniques used are observation, in-depth interviews, and documentation. And to check the validity of the data, researchers used time triangulation during the research process at SDN 2 Mumbul Sari North Lombok. The results showed that in instilling the values of discipline the teacher made a learning contract that was made and agreed upon between the teacher and the students. And students must be able to obey the learning contract that has been made. The teacher also invites students to make sanctions for these violations. So that teachers actively involve students in classroom organizing discipline activities. The sanctions for violations in question are doing questions on the board, giving additional assignments, summarizing lesson material singing songs in front of the class, reciting memorized lesson material in front of the class and bringing students to the teacher's room. Teachers must set a good example, be honest, fair, and match words with actions. Then the obstacles experienced by teachers in